1999
DOI: 10.1071/pp99030
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular and tissue Mn compartmentation in bean leaves under Mn toxicity stress

Abstract: Non-aqueous fractionation was used to characterize subcellular and tissue Mn compartmentation of mature and immature leaves of two common bean (Phaseolus vulgaris L.) cultivars contrasting in their response to Mn toxicity. Excess Mn decreases leaf CO2 assimilation through a reduction of chlorophyll content in immature leaves with no effect detected on mature leaves. We hypothesized that differential accumulation of Mn in chloroplasts occurs at different leaf developmental stages. Chloroplasts of immature leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 38 publications
3
38
2
2
Order By: Relevance
“…Deposition of inorganic and complexed forms of metals in vacuoles constitutes a major mechanism of detoxification (2). A large degree of tissue specificity has been observed in this property, with harmful metals typically accumulating in epidermal tissues (9) and specialized structures such as trichomes (10). Perhaps surprisingly, MTP11 expression is undetectable in these tissues, with expression predominantly in the root tip and leaf hydathodes.…”
Section: Mtp11 Expression Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deposition of inorganic and complexed forms of metals in vacuoles constitutes a major mechanism of detoxification (2). A large degree of tissue specificity has been observed in this property, with harmful metals typically accumulating in epidermal tissues (9) and specialized structures such as trichomes (10). Perhaps surprisingly, MTP11 expression is undetectable in these tissues, with expression predominantly in the root tip and leaf hydathodes.…”
Section: Mtp11 Expression Patternsmentioning
confidence: 99%
“…However, symptoms of Mn toxicity vary widely among plant species, as do critical Mn concentrations at which such symptoms are expressed (6)(7)(8). Plants that tolerate high Mn concentrations can exhibit distinct compartmentation patterns, such as accumulation in the epidermal cell layer (9) and deposition in trichomes (10). In conditions of high Mn supply, plants accumulate high concentrations of the metal in vacuoles (11) and ectopic expression of vacuolar Mn transporters can increase the Mn tolerance of plants (12,13).…”
mentioning
confidence: 99%
“…In a study of four forest species that are Mn hyperaccumulators -Gossia bidwillii, Virotia neurophylla, Macadamia integrifolia and Macadamia tetraphylla -Fernando et al (2006a,b) suggested that the accumulation of the excess Mn in the leaves occurs by storage in the nutrient in the mesophyll cells of the palisade parenchyma (photosynthetically active tissue), as a behavior pattern in these accumulator plants, unlike what occurs with Cu and Ni, which are accumulated in the tissues of the epidermis (trichomas) and in the vacuole (Arru et al, 2004;Broadhurst et al, 2004), and with Zn and Cd, which are accumulated in the vacuoles of the spongy mesophyll cells and apoplast (Küpper et al, 1999;Di Toppi et al, 2005). The accumulation of Mn in the form of oxalate crystals is debatable (González & Lynch, 1999). The scanning electron microscopy images of sections from Mn-deficient leaves, in all the three genotypes, showed a certain degree of tissue disorganization and minor alteration in the epidermis (abaxial and adaxial face), and no stomata reduction in relation of those observed in adequate Mn-supply (2 μmol L -1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study of four forest species that are Mn hyperaccumulators -Gossia bidwillii, Virotia neurophylla, Macadamia integrifolia and Macadamia tetraphylla - Fernando et al (2006a,b) suggested that the accumulation of excess Mn in the leaves occurs by storage of the nutrient in the mesophyll cells of the palisade parenchyma (photosynthetically active tissue), as a behavior pattern in these accumulator plants, in contrast to Cu and Ni, which are accumulated in the epidermis tissues (trichomas) and the vacuole (Arru et al, 2004;Broadhurst et al, 2004), and unlike Zn and Cd, which are accumulated in the vacuoles of the spongy mesophyll cells and apoplast (Küpper et al, 1999;Di Toppi et al, 2005). The accumulation of Mn in the form of oxalate crystals is debatable (González & Lynch, 1999).…”
Section: Resultsmentioning
confidence: 99%